Issues And Challenges Of Ethnicity And Election Outcomes In Nigeria, As Well As The Strategies Model Used By The Apc To Influence The 2015 Presidential Election. - Sulaiman T.H; Abalaka, J.N,; Ajiteru,S.A.R (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study uses a qualitative methodology and secondary source data to investigate election cheating and its impact on Nigeria's democratic consolidation. It will be examined using historical and content analysis. examination. Nigerian democracy's progress has been severely hampered by election tampering. According to the report, e-election holds enormous promise and might be the solution to voter fraud in Nigeria's electoral system provided it is properly deployed and funded. It starts by looking at the constitutional, legal, and theoretical underpinnings of electronic voting. Second, it examines the real-world obstacles to the adoption and deployment of an electronic voting system in Nigeria by learning from other countries. Nigeria's elections have fallen short of expectations thus far because of a variety of electoral manipulations that have prevented the nation from holding legitimate, free, and fair elections within her political system. In addition to undermining Nigeria's democratic consolidation, election cheating has breached the fundamental human right (right to lives) of a large number of Nigerians. This essay offers some crucial suggestions that could solve the issues of election tampering and explain how those actions can support the need for a democratic atmosphere,